2014
DOI: 10.1111/joss.12093
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Free Sorting: A Successful Method with Older Consumers and a Novel Approach to Preference Mapping

Abstract: Taxonomic free sorting (TFS) is a fast, reliable and new technique in sensory science. The method extends the typical free sorting task where stimuli are grouped according to similarities, by asking respondents to combine their groups two at a time to produce a hierarchy. Previously, TFS has been used for the visual assessment of packaging whereas this study extends the range of potential uses of the technique to incorporate full sensory analysis by the target consumer, which, when combined with hedonic liking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…Overall the results suggest that FST allowed the detection of differences in sample categorization in the different age groups of the elderly population and the different countries, and so is applicable for older adults. The present research therefore corroborates the good applicability of sorting methodology with healthy older adults as reported by Withers et al (2014).…”
Section: The Performance Of the Free Sorting Task Among Countries Andsupporting
confidence: 90%
“…Overall the results suggest that FST allowed the detection of differences in sample categorization in the different age groups of the elderly population and the different countries, and so is applicable for older adults. The present research therefore corroborates the good applicability of sorting methodology with healthy older adults as reported by Withers et al (2014).…”
Section: The Performance Of the Free Sorting Task Among Countries Andsupporting
confidence: 90%
“…When comparing to the classical approach some authors concluded that these methods give similar results to external preference mapping. Other applications using rapid methods can be found in Varela, Beltrán, and Fiszman (2014), using preference ranking and open comments in Withers et al (2014)), and using taxonomic free sorting and liking in Faye et al (2006) with focus on liking of textiles.…”
Section: Introductionmentioning
confidence: 99%
“…Preference maps have been used extensively for many types of sensory marketing and product development studies for determining drivers of liking (Hwang & Hong, ; Jervis et al, ; Kim & Kim, ; Kim, Lee, Kwak, & Kang, ; Villamor, Daniels, Moore, & Ross, ; Withers et al, ), product quality and optimization (Delgado and Guinard, ; Lawless, Threlfall, Meullenet, & Howard, ; Mahanna & Lee, ; Neely, Lee, & Lee, ), and the introduction of new products into a blank space on a map (de Morais & Pereira ; Donadini & Fumi, ). Delgado and Guinard, , Zhang et al (), Leksrisompong, Lopetcharat, Guthrie, and Drake (), and Paulsen, Næs, Ueland, Rukke, and Hersleth () interpreted a preference map based only on its configuration.…”
Section: Introductionmentioning
confidence: 99%